EFFICIENCY ASSESSMENT OF REMEDIATION ACTIONS IN THE SITE OF SUBSURFACE CONTAMINATION WITH PETROLEUM PRODUCTS WITHIN THE FUEL AND LUBRICANTS WAREHOUSE OF BORYSPIL AIRPORT - Shpak, O.; Havryliuk, R.; Lohvynenko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper is devoted to the topical problem of remediation of the subsurface contaminated with petroleum products. Subsurface contamination with petroleum products on the territory of the fuel and lubricants warehouse of Boryspil Airport in the form of the aviation kerosene lens has occured for a long time. Remediation works on the removal of mobile petroleum products and contaminated groundwater, which were carried out at the research site, did not allow to completely eliminate contamination. To determine the efficiency of liquidation pumping of mobile petroleum products and groundwater, the volume and state of petroleum products in soil and their transformation under the influence of groundwater level fluctuations were assessed. Using the method we developed, the minimum value of the thickness of a petroleum product layer in a well, at which mobile petroleum products are absent in soil and liquidation pumping becomes inefficient, was calculated,. According to the monitoring data and calculation of the kerosene volume in the lens, liquidation pumping on the contaminated area led to the stabilization of contamination spreading and reduction of the aviation kerosene lens area.
Keywords: remediation; geological environment; contamination; petroleum products; liquidation pumping